2012
DOI: 10.1094/mpmi-10-11-0265
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Class III Peroxidase and the Mitochondrial Protein TSPO in Oxidative Burst Upon Treatment of Moss Plants with a Fungal Elicitor

Abstract: Production of apoplastic reactive oxygen species (ROS), or oxidative burst, is among the first responses of plants upon recognition of microorganisms. It requires peroxidase or NADPH oxidase (NOX) activity and factors maintaining cellular redox homeostasis. Here, PpTSPO1 involved in mitochondrial tetrapyrrole transport and abiotic (salt) stress tolerance was tested for its role in biotic stress in Physcomitrella patens, a nonvascular plant (moss). The fungal elicitor chitin caused an immediate oxidative burst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 56 publications
5
60
0
Order By: Relevance
“…In contrast, treatment with the fungal PAMP chitin or its derivative chitosan induced phosphorylation and activation, assayed by phosphorylation of the general kinase substrate MBP, of two P. patens MPKs within 1 min (Supplemental Figures 1A and 1C). These findings are in line with those of Lehtonen et al (2012Lehtonen et al ( , 2014 showing that chitosan triggers responses in P. patens including a ROS burst, defense transcript accumulation, and secretion of pathogen response proteins. In addition, these MPKs were rapidly phosphorylated in response to bacterial peptidyl glycans (PGNs; Supplemental Figure 1D), which have molecular patterns similar to chitin.…”
Section: Phosphorylation and Activation Of P Patens Mpks In Responsesupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, treatment with the fungal PAMP chitin or its derivative chitosan induced phosphorylation and activation, assayed by phosphorylation of the general kinase substrate MBP, of two P. patens MPKs within 1 min (Supplemental Figures 1A and 1C). These findings are in line with those of Lehtonen et al (2012Lehtonen et al ( , 2014 showing that chitosan triggers responses in P. patens including a ROS burst, defense transcript accumulation, and secretion of pathogen response proteins. In addition, these MPKs were rapidly phosphorylated in response to bacterial peptidyl glycans (PGNs; Supplemental Figure 1D), which have molecular patterns similar to chitin.…”
Section: Phosphorylation and Activation Of P Patens Mpks In Responsesupporting
confidence: 90%
“…To assess whether the levels of pathogen defense-related transcripts were altered in Dmpk4a, we measured the response to chitosan of five transcripts involved in defense against pathogens and/or are induced in response to chitosan in both Arabidopsis and P. patens: PAL4, CHS, ERF2, a-DOX, and LOX7 (Oliver et al, 2009;Lehtonen et al, 2012;Machado et al, 2015;Overdijk et al, 2016). Although the response to chitosan (Supplemental Figures 14A and 14B) is slower than to chitin ( Figure 4E), all these transcripts accumulated less in Dmpk4a compared with the wild type (Supplemental Figures 14A to 14E).…”
Section: Characterization Of Moss Mpk4a In Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, P. patens is directly accessible to manipulations or diverse treatments because most of the tissues consist of single cell layers (phylloids) or filaments (protonema) that are able to take up water and nutrients over the whole surface. Therefore, P. patens is a suitable model plant to analyse phytohormone action (Decker et al, 2006) and responses to biotic (Lehtonen et al, 2012) as well as abiotic stresses (Frank et al, 2005).…”
Section: Moss Transgenesis 555mentioning
confidence: 99%
“…2). Further evidence for peroxidases as a source of pathogen-induced ROIs emerged from a recent study in the moss Physcomitrella patens, where it was shown that Prx34 not only catalyzes ROI production but is also required for antifungal resistance (23). It must be noted that this peroxidase is unrelated to the previously mentioned Arabidopsis PRX33/34 (24) and the same gene nomenclature is purely coincidental.…”
Section: Prx34 (4)mentioning
confidence: 98%